Does foreign ownership decrease bank risk? Evidence from Vietnam - Nguyen , Tran Xuan Linh; Le , Thi Lan (Journal of Finance - Marketing Research, 2025)
Based on data from 23 Vietnamese commercial banks in the period 2012-2022, the study used the Bayesian method to provide evidence of the positive impact of the foreign investment capital ratio on bank stability. Specifically, increasing the foreign capital ratio enhances risk resilience and strengthens the banks’ overall financial stability. This is significant for policymakers, who should consider relaxing regulations on the ceiling for foreign capital ratios. By attracting more foreign investment, banks can leverage strong financial resources and advanced management expertise from international investors. However, to achieve these benefits, flexible and appropriate policies are needed to facilitate the attraction of foreign investment. Policymakers must carefully consider the risks and benefits, ensuring that new regulations do not cause unintended instability in the banking system. In summary, increasing the foreign capital ratio is a crucial step towards enhancing Vietnamese commercial banks’ stability and sustainable development.